2017
DOI: 10.1017/s1049023x17006914
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Mycosis due to Exposure toEurotium herbariorumafter the Great East Japan Earthquake

Abstract: This report presents the rare case of a patient who developed allergic bronchopulmonary mycosis (ABPM) due to exposure to E. herbariorum during temporary housing after the Great East Japan Earthquake. Oshikata C , Watanabe M , Saito A , Ishida M , Kobayashi S , Konuma R , Kamata Y , Terajima J , Cho J , Yanai M , Tsurikisawa N . Allergic bronchopulmonary mycosis due to exposure to eurotium herbariorum after the Great East Japan Earthquake. Prehosp Disaster Med. 2017;32(6):688-690.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Regarding the disastrous heavy rainfall that occurred in Western Japan in 2018, Oda et al reported that Legionella pneumonia occurred during recovery work, possibly caused by exposure to water and soil after the flood disaster (5). In addition, Oshikata et al reported a case of allergic bronchopulmonary mycosis that developed due to exposure to Eurotium herbariorum after the Great East Japan Earthquake, in which mycofloral surveillance was performed and high counts of Eurotium were detected (6). The present case seems to be similar and interesting in that the presence of the antigen was proven through an environmental survey.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Regarding the disastrous heavy rainfall that occurred in Western Japan in 2018, Oda et al reported that Legionella pneumonia occurred during recovery work, possibly caused by exposure to water and soil after the flood disaster (5). In addition, Oshikata et al reported a case of allergic bronchopulmonary mycosis that developed due to exposure to Eurotium herbariorum after the Great East Japan Earthquake, in which mycofloral surveillance was performed and high counts of Eurotium were detected (6). The present case seems to be similar and interesting in that the presence of the antigen was proven through an environmental survey.…”
Section: Discussionsupporting
confidence: 58%
“…Stenotrophomonas maltophilia, Burkholderia cepacian, Scedosporium, and Aspergillus sp. during recovery work (6).…”
Section: Introductionmentioning
confidence: 99%
“…Due to allergen avoidance through environmental improvement after floods, asthma symptoms in children diminished [31] and respiratory function increased [32]. Similarly, we reported in case presentation that the temporary housing environment in Ishinomaki city has improved greatly, thereby decreasing fungal exposure and ameliorating symptoms of allergic bronchopulmonary mycosis [21]. A meta-analysis showed that bronchial hyperresponsiveness decreased after mite-impermeable mattress covers were provided to patients previously exposed to high levels of Der 1 [33].…”
Section: Discussionmentioning
confidence: 69%
“…In addition, a nuclear accident at the Fukushima Daiichi Nuclear Power Plant after the earthquake and tsunami forced an evacuation, and levels of indoor airborne fungi were found to be increased in the evacuation zone [20]. We previously reported a rare case of allergic bronchopulmonary mycosis in a patient exposed to the fungusEurotium herbariorum while living in post-earthquake temporary housing in Ishinomaki [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fungal community analyses in households have begun to attract attention because fungi are now generally considered to be allergens [ 5 , 6 ]. Many researchers have previously reported cases of patients with asthma, allergic bronchopulmonary mycosis (ABPM) and other illnesses caused by fungal products [ 7 , 8 ]. Currently, the culture method remains the primary approach used to conduct fungal community analysis for dwellings [ 9 , 10 , 11 ] and the application of molecular methods, including the NGS method, remains limited because the sequence registrations for fungi in databases are incomplete, and the procedures and methods used to identify fungal sequences have not yet been standardized [ 12 ].…”
Section: Introductionmentioning
confidence: 99%